Cities and the governance of transport interfaces: Ethiopia's new rail systems. (June 2020) - Rode, Philipp; Terrefe, Biruk; da Cruz, Nuno F.
Abstract: This paper investigates the governance of transport infrastructure interfaces. These are connection or touching points that bring together different city systems, technical characteristics and governance regimes. The empirical evidence comes from Ethiopia's new rail systems and is based on experiences in two cities, the capital Addis Ababa and the second largest city Dire Dawa. The techno-spatial and organisational boundaries that define infrastructure interfaces are under-researched across disciplines. Yet it is at these hotspots of urban governance where many critical questions for cities arise: who governs, what to prioritise, how to coordinate? Based on a multiple case study approach, this paper combines socio-spatial analysis with institutional analysis of infrastructure governance. The findings include the identification of highly centralised and hierarchical governance and coordination dynamics, as well as the critical role of a new bureaucracy (the Ethiopian Railway Corporation) structured around core railway engineering competence rather than urban transport and development expertise. More generally, it is a techno-political alliance in Ethiopia which shapes urban development and the rollout of infrastructure at an unprecedented speed and scale. Highlights: Transport interfaces are useful entry points to analyse urban governance. Ethiopia managed to design and build complex rail systems at a very fast pace. As a trade-off there was very little coordination with other sectors & stakeholders. The federal government centralised decisions and city authorities were overruled. Urban development in Ethiopia is highly technocratic & backed by political leaders.